Anion-regulated cobalt coordination polymer: Construction, electrocatalytic hydrogen evolution and L-cysteine electrochemical sensing. (10th July 2022) - Wu, Huilu; Shen, Qinqin; Dong, Jianping; Zhang, Geng; Sun, Fugang; Li, Ruixue
Highlights: Three anion-regulated Co(II) coordination polymers with determinate and adjustable structures based on new bisbenzimidazole have been synthesized. CPs 1–3 show a two-dimensional layer, one-dimensional hollow column and a two-dimensional sawtooth layer structure, respectively. CPs 1–3 show effective catalysis for hydrogen evolution reaction. The relationship between coordinated water molecules and HER catalytic properties was explored. CPs 1–3 show effective recognition of L-cysteine. Abstract: Considering that the construction of molecular catalysts with regulatory and determinate structural are conducive to the rapid development of electrical/chemical energy conversion system. Three anion-regulated Co(II) coordination polymers (CPs 1–3 ) with the chemical compositions of {[CoL(tp)(H2 O)2 ]2H2 O} n (1), {[Co8 L4 (btc)4 (H2 O)16 ](formate)(btc)DMF0.5MeOH0.5Me2 NH36.5H2 O} n (2), and {[Co2 L(fum)2 (H2 O)2 ]2DMF3H2 O} n (3) (L = bis(1-(pyridin-4-ylmethyl)-benzimidazol-2-ylmethyl)ether, tp = terephthalate, btc = 1, 3, 5-benzenetricarboxylate, fum = fumarate), have been synthesized using the solvothermal method by introducing different anion. Single crystal analysis shows that the CPs 1 and 3 possess 2D layer structure, while CP 2 shows 1D hollow column structure. The electrocatalytic hydrogen evolution and the L-cysteine electrochemical sensing properties of carbon paste electrode modified with Co(II) CPs (CPEs 1–3 ) were investigated respectively. The hydrogen evolution reaction (HER) properties of CPEs 1–3 were studied in 0.5 M H2 SO4, the results show that 1–3 exhibit overpotentials of –695, –780 and –801 mV at the current density of 10 mA cm –2 with Tafel slopes of 210 ∼ 273 mA dec –1, which confirming that they all have effective electrocatalytic HER ability. The catalytic mechanism of CPs 1–3 was inferred from the determined structure, which showing that the reason for the catalytic performance order of 1 > 2  ≥ 3 may be due to the difference in the number of coordinated water molecules. E lectrochemical sensing studies show that CPs 1–3 have low detection limits of 0.43, 0.78, and 0.65 μM for l -cysteine ​​in the response ranges of 0.5 μM ∼ 4.0 mM, 1 μM ∼ 4.0 mM, and 1 μM ∼ 4.0 mM, and sensitivity of 8.09, 7.20 and 10.84 μA mM –1 . Therefore, the three Co(II) coordination polymers are effective dual-functional electrocatalysts. Graphical abstract: The synthesis of high-efficiency electrocatalysts is the key to achieving high current density at low overpotentials in electrochemical processes. Therefore, three new Co(II) coordination polymers (CPs 1–3 ) with two-dimensional layers and one-dimensional hollow column structures have been successfully synthesized by introducing different anions. The research on the electrochemical activity of CPs 1–3 is achieved by manufacturing modified carbon paste electrodes (CPEs 1–3 ). The results show that the required overpotentials of 1–3 are –695 ∼ –801 mV at 10 mA cm –2 in electrocatalytic hydrogen evolution reaction. For electrochemical sensing of l -cysteine, 1–3 all showed a good recognition effect, of which the detection limit of CP 1 can reaches 0.43 μM in the response range of 0.5 μM ∼ 4.0 mM. Therefore, CPs 1–3 can be considered as effective dual-function electrocatalysts. Image, graphical abstract